Research Skills of the Professorial Lecturers: Input to Capability Building - Bueno, David (JPAIR Institutional Research, 2017)
To achieve an effective graduate educational reform, faculty development emerged as a key factor. It facilitates the professional and instructional growth of lecturers and promotes improvement in the institution through helping them become contributors to the school’s mission. The study was designed to determine the research skills of graduate professors based on the Expected Performance Standards (EPS) set by one private Higher Education Institution (HEI) as input to training and development. The descriptive-cross-sectional design and descriptive statistical analysis were used. The teaching outcomes were based on the average performance from the three assessments conducted by the Dean among the professors during the academic year 2014-2015. The results exposed that the faculty were outstanding in achieving the objectives of the graduate program by showing mastery of subject matter, relating current issues and community needs, and participating the activities of professional organizations. However, they were just satisfactory in demonstrating mastery of research skills in relation to research output, assisting graduate students in developing research competencies, and showing professional growth through research activities and publications. These are essential inputs to training and development program to continually upgrade the professorial lecturers’ research preparation, dissemination and utilization.